Discovery of Shamshevia Grichanov in the Oriental Region (Diptera: Dolichopodidae) - Grichanov, Igor Ya. (Zootaxa, 2012)
The formerly Afrotropical genus Shamshevia Grichanov, 2012, is recorded from the Oriental Region for the first time.Description of a new species Shamshevia reshchikovi sp. nov. from India is provided. A modified diagnosis of the genus is compiled.